Development of Destination Branding with Unique Selling Proposition Approach: A Case Study at Kampung Adat Ratenggaro, NTT - Caesar Achmad Firjaun Faqih Aziz; Yumna Alifa; Pringgo Dwiyantoro; Banung Grahita (Research and Community Service Center, Politeknik Pariwisata NHI Bandung, 2025)
This study explores on the development of destination branding for Kampung Adat Ratenggaro, a traditional village in East Nusa Tenggara, Indonesia, using the Unique Selling Proposition (USP) approach. The research aims to identify and leverage the village's cultural and natural assets to create a compelling brand identity. The scope includes an analysis of current tourism conditions, strategic opportunities, and the formulation of branding strategies tailored to highlight destination uniqueness. A qualitative approach was employed, incorporating SOAR analysis using Internal & External Factor Analysis Summary to prioritize strategic initiatives and mapping strengths, weaknesses, opportunities, and aspirations. Key findings reveal that Kampung Adat Ratenggaro holds significant potential as a cultural tourism destination, supported by its architectural heritage, traditional weaving, and vibrant ceremonies. The proposed branding concept,